Local community water providers universalize access and reduce poverty - Ballestero, Maureen (2013)
This article develops two themes: the link between access to water and poverty, and the role of community organizations enabling access to water in rural and periurban communities of Costa Rica. It states that access to drinking water service is associated to poverty reduction, and economic and social development. It describes the emergence and evolution of local organizations, which arise from the inability of AyA and municipalities to enable water access to poor communities. Finally, it highlights the importance of visualize these local bodies as agents of development and prioritizes of sector reforms.